الذكاء الاجتماعي والوجداني كمُنبئات بالسلوك الإيثاري لدى عينة من طلاب وطالبات الجامعة‪‪ - الشهري، يزيد محمد حسن (دار سمات للدراسات والأبحاث, 2015)
هدفت الدراسة إلى الوقوف على طبيعة العوامل الوجدانية والاجتماعية من حيث العلاقة وإمكانية التنبؤ من خلالها بالسلوك الإيثاري. وتكونت عينة الدراسة الحالية من مجموعتين إحداهما مجموعة الطلاب (90) والأخرى مجموعة الطالبات (90) من كلية التربية والدبلوم العام في التربية بجامعة جدة. ولقد استخدم في الدراسة مقياس الذكاء الاجتماعي ومقياس الذكاء الوجداني (1) ومقياس السلوك الإيثاري (2). وقد أسفرت نتائج الدراسة عن وجود علاقة ارتباطية ذات دلالة إحصائية بين كل من الذكاء الاجتماعي والذكاء الوجداني في علاقتها بالسلوك الإيثاري. كما أنه توجد فروق ذات دلالة إحصائية بين عينة الدراسة في كل من الذكاء الاجتماعي والذكاء الوجداني والسلوك الإيثاري باختلاف الجنس. وأخيرا توصلت الدراسة إلى أن كل من الذكاء الاجتماعي والذكاء الوجداني يسهم في التنبؤ بالسلوك الإيثاري. كما وتوصي الدراسة بالاهتمام بغرس وتنمية السلوك الإيثاري منذ الصغر. وتنمية الذكاء الاجتماعي والوجداني عبر البرامج التنموية لفئة طلبة الجامعة لما لها من تأثير قوي في رفع معدلات التوافق النفسي والاجتماعي. وتفعيل الأعمال التطوعية والمشاركة الاجتماعية الإيجابية للطلبة مما يعزز روح التعاون الجماعي وينمي الذكاء الاجتماعي.‪‪
The current study aimed to know the nature of emotional & social factors, its relation with altruistic behavior, and the ability to predict this altruistic behavior through this relation. The sample consisted of two groups, the first group consisted of 90 students from the Faculty of Education and General Diploma in Education at Jeddah University. the second group consisted of 90 female students from the College of Education and General Diploma in Education at Jeddah University, the results of the study showing that there is a statistical significance relation between social intelligence , & emotional intelligence with altruistic behavior. There are significant differences between the study sample in social, emotional intelligence & altruistic behavior depending the differences on sex. The Social & emotional intelligence contributes in predicting altruistic behavior among a sample study of students in the university. The study recommended that we should give some interest in developing and improving the altruistic behavior from the early ages of our children, we should also improve social & emotional intelligence among the university students through the developmental programs in order to improve social and psychological adjustment. Also the study recommended that we should improve volunteers works and community participation for university students in order to improve the soul of cooperation for developing social intelligence.
Keywords: الذكاء الاجتماعي‪‪ -- الذكاء الوجداني‪‪ -- السلوك الإيثاري‪‪ -- طلبة الجامعات‪‪